2013
DOI: 10.1016/j.adolescence.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Trust and social reciprocity in adolescence – A matter of perspective‐taking

Abstract: Changes in social behaviour from childhood to adulthood have been suggested to be driven by an increased sensitivity to others' perspectives. Yet, the link between perspective‐taking and social processes, such as trust and reciprocity, has rarely been investigated during adolescence. Using two trust games with a cooperative and an unfair counterpart and an online perspective‐taking task with 50 adolescents, we show that those with a higher perspective‐taking tendency demonstrate greater trust towards others an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 48 publications
(90 reference statements)
7
105
2
2
Order By: Relevance
“…Alternatively, it could be that adults are better at adjusting their thinking to overcome an egocentric bias, rather than that this bias no longer exists (Epley, Morewedge, & Keysar, 2004). In a recent study, Fett et al (2014) found no age-related differences in a sample of 13-18-year-olds, but observed that performance in the Director task was significantly associated with adolescents' behaviour in a trust game with cooperative and unfair counterparts, providing evidence for the ecological validity of the Director task.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Alternatively, it could be that adults are better at adjusting their thinking to overcome an egocentric bias, rather than that this bias no longer exists (Epley, Morewedge, & Keysar, 2004). In a recent study, Fett et al (2014) found no age-related differences in a sample of 13-18-year-olds, but observed that performance in the Director task was significantly associated with adolescents' behaviour in a trust game with cooperative and unfair counterparts, providing evidence for the ecological validity of the Director task.…”
mentioning
confidence: 92%
“…, or using age as a continuous measure (e.g. Fett et al, 2014). Using three age groups within this study enabled exploration which showed that mid-adolescents were similar to the young adolescents for perspectivetaking (i.e.…”
Section: Distinct Developmental Trajectoriesmentioning
confidence: 99%
“…Interesting data were obtained by Fett et al [61], who showed that the ability of teenagers to change perspective in cooperation tests is associated with a more pro-social behavior and higher level of trust to partners. A group of Italian researchers headed by one of the au-Kholomogorova A.B.…”
Section: Referring To Work Of His Contemporary Ab Zalkind Who Studmentioning
confidence: 98%
“…Pirma, paaugliai mentalizacijos gebėjimus naudoja lanksčiau, jiems prireikia mažiau išteklių ir laiko pasinaudoti kai kuriais gebėjimais "čia ir dabar", kaip antai emocijų atpažinimu, ypač veido teikiamos informacijos apdorojimu (Kilford et al, 2016). Antra, atskiros mentalizacijos dimensijos ir jų poliai integruojami ir tarpusavyje, ir su kitais gebėji-mais, tokiais kaip vykdomosios funkcijos, emocijų reguliacija, prosocialus elgesys (Crone, Bullens, van der Plas, Kijkuit, & Zelazo, 2008;Fett et al, 2014;Im-Bolter, Agostino, & Owens-Jaffray, 2016;Overgaauw, Güroğlu, Rieffe, & Crone, 2014). Remiantis minėtų autorių (Badoud et al, 2016) svarstymais bei pastarųjų metų tyrimais socialinio pažinimo bei neuromokslo srityse, galima teigti, kad paauglystės laikotarpiu mentalizacijos kaip daugiadimensio gebėjimo raida intensyviausia dviem požiūriais.…”
Section: Mentalizacijos Raida Ir Sklaida Paauglystėjeunclassified
“…perspective taking) plėtra (Fett et al, 2014). Vėlgi, gebėjimo atsižvelgti į kito žmogaus požiūrį pagrindas randasi vaikystėje, tačiau gebėjimo naudotis šia kompetencija "čia ir dabar" raida tęsiasi paauglystėje (Kilford et al, 2016).…”
Section: Mentalizacijos Raida Ir Sklaida Paauglystėjeunclassified